Assessment of Urban Vulnerability to Flooding Using Multi-Criteria Analysis: The Case Study of El Bayadh City, Algeria - Hallil, A.; Redjem, A. (Engineering, Technology & Applied Science Research, 2022)
Urban vulnerabilities must be studied and assessed to make cities more resilient to floods. This study aimed to assess the urban vulnerability of El Bayadh city, located in the west of Algeria, to floods and to identify flood-prone areas. Using the Hierarchical Multi-criteria Analysis (HMA) method, a set of criteria was proposed such as population density, housing typology, type of equipment, and road network to measure the overall fragility of the study area. The Geographic Information System (GIS) was used to translate the obtained results and develop the global vulnerability map. The most important results were: 5.6% of the study area had an extreme vulnerability, 7.97% high vulnerability, 8.5% medium vulnerability, and 77.87% low vulnerability. The results of this study can be used as a tool to assist local authorities during decision-making regarding flood danger assessment.